Utility of a single early warning score in patients with sepsis in the emergency department. Issue 6 (9th March 2013) - Corfield, Alasdair R; Lees, Fiona; Zealley, Ian; Houston, Gordon; Dickie, Sarah; Ward, Kirsty; McGuffie, Crawford; ,
Abstract : Background: An important element in improving the care of patients with sepsis is early identification and early intervention. Early warning score (EWS) systems allow earlier identification of physiological deterioration. A standardised national EWS (NEWS) has been proposed for use across the National Health Service in the UK. Aim: To determine whether a single NEWS on emergency department (ED) arrival is a predictor of outcome, either in-hospital death within 30 days or intensive care unit (ICU) admission within 2 days, in patients with sepsis. Methods: Data were collected over a 3-month period as part of a national audit in 20 EDs in Scotland. All adult patients who were admitted for at least 2 days or who died within 2 days were screened for sepsis criteria. Patients with systemic inflammatory response syndrome criteria were included. An EWS was calculated based on initial physiological observations made in the ED using the NEWS. Results: Complete data were available for 2003 patients. Each rise in NEWS category was associated with an increased risk of mortality when compared to the lowest category (5–6: OR 1.95, 95% CI 1.21 to 3.14), (7–8: OR 2.26, 95% CI 1.42 to 3.61), (9–20: OR 5.64, 95% CI 3.70 to 8.60). This was also the case for the combined outcome (ICU and/or mortality). Conclusions: An increased NEWS on arrival at ED is associated with higher odds of adverse outcome among patients with sepsis. The use of NEWS could facilitate patient pathways to ensure triage to a high acuity area of the ED and senior clinician involvement at an early stage.